Optimising cover system performance with native vegetation at Mt. Whaleback mine to minimise acid and metalliferous drainage risk: a research consortium approach - Johnson, B.; Gale, J.; Mejia, R.; Veneklaas, E.; Leopold, M.; Barteaux, M.; Phillip, M.; Cooper, H.; Erickson, T.E.; Gibson, D.; Clark, M.; Stock, E.; et al. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Acid mobilisation due to net percolation (NP) through overburden storage areas poses a significant environmental risk at mine sites. BHP aims to minimise this risk at Mt. Whaleback and other Western Australia Iron Ore (WAIO) sites with the revegetated cover system program (RCSP), to improve understanding of vegetation-substrate interactions that affect transpiration and their impact on NP. The RCSP employs a crossdisciplinary approach, and includes research partners from BHP, Okane Consultants, and The University of Western Australia. The RCSP seeks to: Quantify the effect of specific vegetation prescriptions and functional types on NP reduction through transpiration. Define how soil spatiotemporal processes influence evapotranspiration and NP partitioning within cover systems. Refine model parameters and test assumptions on plant traits influencing water movement. Ensure that research outcomes are practical and scalable for BHP implementation. Key project outcomes will be assessed through a field trial constructed at Mt. Whaleback mine. The field trial includes 18 vegetated cover trial plots, including three lysimeters. Automated monitoring collects data on weather, soil volumetric water content and matric potential, and lysimeter NP; electrical resistivity tomography arrays provide an integrated soil moisture understanding at several plots. An irrigation system allows for the simulation of ecologically informed rainfall events and ensures seedling emergence and plant establishment is maximised. The native vegetation treatments for the cover trial include specific mixes of plant species to optimise transpiration: grassland, grassland with woody shrubs and trees, and a nonvegetated control. This paper outlines the objectives, approach, and methodology of the vegetated cover trial. The RCSP will deliver practical and scalable solutions for optimising cover system transpiration, minimising NP, and reducing acid and metalliferous drainage risk at WAIO mine sites. The project will provide valuable insights into vegetation-substrate interactions, refine cover system design tools, and contribute to the development of sustainable mine closure practices.